2010
DOI: 10.1093/aob/mcq156
|View full text |Cite
|
Sign up to set email alerts
|

Mycoheterotrophy evolved from mixotrophic ancestors: evidence in Cymbidium (Orchidaceae)

Abstract: It is demonstrated for the first time that mycoheterotrophy evolved after the establishment of mixotrophy rather than through direct shifts from autotrophy to mycoheterotrophy. This may be one of the principal patterns in the evolution of mycoheterotrophy. The results also suggest that the establishment of symbiosis with ectomycorrhizal fungi in the lineage leading to mixotrophic Cymbidium served as pre-adaptation to the evolution of the mycoheterotrophic species. Similar processes of nutritional innovations p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 34 publications
3
75
0
1
Order By: Relevance
“…The mycoheterotrophic Aphyllorchis montana and A. caudata from Thailand grow in tropical dipterocarpacean forests, and are associated with diverse ECM fungi including Sebacinales (Roy et al 2009). Ogura-Tsujita and Yukawa (in Motomura et al 2010) found a shift to exclusively ECM mycobionts, including sebacinoids, in apochlorotic, mycoheterotrophic Cymbidium species in Japan. A general conclusion was that mycoheterotrophy evolved from mixotrophic ancestors and not directly from autotrophic ones in these orchids.…”
Section: Mycoheterotrophic and Mixotrophic Orchidsmentioning
confidence: 98%
“…The mycoheterotrophic Aphyllorchis montana and A. caudata from Thailand grow in tropical dipterocarpacean forests, and are associated with diverse ECM fungi including Sebacinales (Roy et al 2009). Ogura-Tsujita and Yukawa (in Motomura et al 2010) found a shift to exclusively ECM mycobionts, including sebacinoids, in apochlorotic, mycoheterotrophic Cymbidium species in Japan. A general conclusion was that mycoheterotrophy evolved from mixotrophic ancestors and not directly from autotrophic ones in these orchids.…”
Section: Mycoheterotrophic and Mixotrophic Orchidsmentioning
confidence: 98%
“…Thus, part of their biomass is derived from mycorrhizal fungi, in a nutrition called partial mycoheterotrophy or mixotrophy (MX; see Selosse and Roy 2009 for review). MX species also occur out of Neottieae, and interestingly, MH species are often phylogenetically nested within them, e.g., in the orchid genera Platanthera (Yagame et al 2012) and Cymbidium orchids (Motomura et al 2010), and in Ericaceae (Tedersoo et al 2007). Thus, MX nutrition is often considered as a predisposition to MH evolution , and albinos furnish relevant candidates for a further step during transition to full heterotrophy.…”
Section: Introductionmentioning
confidence: 99%
“…of the tribe Neottieae (Bidartondo et al, 2004;Julou et al, 2005), and in Cymbidium spp. of the tribe Cymbidieae (Motomura et al, 2010). In mycoheterotrophic and mixotrophic orchids, ectomycorrhiza (ECM)-forming fungi, such as Sebacinales, Russulaceae and Thelephoraceae, are most often identified as mycobionts, suggesting that the photosynthates of nearby trees likely represent the final carbon sources.…”
Section: Introductionmentioning
confidence: 99%